AUDIT OF TRUSTWORTHY DIGITAL ARCHIVAL REPOSITORIES - Machado dos Santos, Henrique (Informação em Pauta, 2019)
This study discusses the implementation of archival repositories that conform to the Open Archival Information System and the need to audit them to assess their reliability. To this end, a bibliographic survey of previously published materials is carried out, with selection of: books that approach the perspectives of Archival science in the digital age and the challenge of reliable documentary custody; technical publications such as International Organization for Standardization and auditing standards; and scientific articles retrieved by the Google Scholar search tool, with thematic search related to the preservation of digital archival records, reliable digital repositories, information auditing and archival auditing. The archival repository is the prism of the discussion, since the comparison between the audit standards becomes the guiding category, thus, we obtain a no systematic review article. Thus, the audit standards are analyzed: Trustworthy Repository Audit & Certification: Criteria and Checklist, Catalog of Criteria for Trusted Digital Repositories from Network of Expertise in long-term STORage, Digital Repository Audit Method Based on Risk Assessment and Audit and Certification of Trustworthy Digital Repositories. Finally, a comparison of standards demonstrates that the Audit and Certification of Trustworthy Digital Repositories is best suited for auditing digital archival repositories.